Estimation of radiation exposure to personnel in nuclear medicine during 131| ablation procedure: comparison between direct and indirect methods - Mohamad, Nurul Ashikin (Universiti Sains Malaysia, 2015)
This study focused on measurement of exposure rates to personnel in Nuclear Medicine during 131l ablation procedures using direct and indirect methods. 9 patients undergoing 131l ablation procedures with average activity 131.11 mCi were randomly selected in this study. The direct method of exposure rate measurement was conducted using survey meter (Victoreen 415P-RYR) at various distances (1.0 m, 1.5 m and 2.0 m) from the patients at thyroid and abdomen region. The indirect method of exposure rate measurement was conducted using mathematical model of exposure rate. The result showed that exposure rates decreased with the increased in distance for both direct and indirect methods. The exposure rate of thyroid and abdomen for direct method was higher than indirect method at all distances. The percentage difference between direct and indirect method for various distance were 22.39% ± 2.04 (1.0 m), 16.37% ± 1.38 (1.5 m) and 34.04% ± 3.64 (2.0 m) respectively. Percentage difference of low activity (80 mCi) was significantly decreased with increased time while the percentage difference in medium (120 mCi) and high activity (175 mCi) were significantly decreased as the time increased. The exposure rate between thyroid and abdomen increased at higher 5.32% ± 0.284 (120 mCi), 11.67% ± 0.345 (175 mCi). As conclusion, this study provides useful indicator of occupational exposure to personnel that can be used as guidance for personnel attending patients in radioiodine wards.